Kaon electromagnetic form factors in dispersion theory - D. Stamen; D. Hariharan; M. Hoferichter; B. Kubis; P. Stoffer (European Physical Journal C: Particles and Fields, 2022)
Abstract The electromagnetic form factors of charged and neutral kaons are strongly constrained by their low-energy singularities, in the isovector part from two-pion intermediate states and in the isoscalar contribution in terms of $$\omega $$ ω and $$\phi $$ ϕ residues. The former can be predicted using the respective $$\pi \pi \rightarrow {{\bar{K}}} K$$ π π → K ¯ K partial-wave amplitude and the pion electromagnetic form factor, while the latter parameters need to be determined from electromagnetic reactions involving kaons. We present a global analysis of time- and spacelike data that implements all of these constraints. The results enable manifold applications: kaon charge radii, elastic contributions to the kaon electromagnetic self energies and corrections to Dashen’s theorem, kaon boxes in hadronic light-by-light (HLbL) scattering, and the $$\phi $$ ϕ region in hadronic vacuum polarization (HVP). Our main results are: $$\langle r^2\rangle _\text {c}=0.359(3)\,\text {fm}^2$$ ⟨ r 2 ⟩ c = 0.359 ( 3 ) fm 2 , $$\langle r^2\rangle _\text {n}=-0.060(4)\,\text {fm}^2$$ ⟨ r 2 ⟩ n = - 0.060 ( 4 ) fm 2 for the charged and neutral radii, $$\epsilon =0.63(40)$$ ϵ = 0.63 ( 40 ) for the elastic contribution to the violation of Dashen’s theorem, $$a_\mu ^{K\text {-box}}=-0.48(1)\times 10^{-11}$$ a μ K -box = - 0.48 ( 1 ) × 10 - 11 for the charged kaon box in HLbL scattering, and $$a_\mu ^\text {HVP}[K^+K^-, \le 1.05\,\text {GeV}]=184.5(2.0)\times 10^{-11}$$ a μ HVP [ K + K - , ≤ 1.05 GeV ] = 184.5 ( 2.0 ) × 10 - 11 , $$a_\mu ^\text {HVP}[K_SK_L, \le 1.05\,\text {GeV}]=118.3(1.5)\times 10^{-11}$$ a μ HVP [ K S K L , ≤ 1.05 GeV ] = 118.3 ( 1.5 ) × 10 - 11 for the HVP integrals around the $$\phi $$ ϕ resonance. The global fit to $${{\bar{K}}} K$$ K ¯ K gives $${{\bar{M}}}_\phi =1019.479(5)\,\text {MeV}$$ M ¯ ϕ = 1019.479 ( 5 ) MeV , $${\bar{ \varGamma }}_\phi =4.207(8)\,\text {MeV}$$ Γ ¯ ϕ = 4.207 ( 8 ) MeV for the $$\phi $$ ϕ resonance parameters including vacuum-polarization effects.